Dramatizamos un cuento, fiesta en el cielo - Amay Sanchez, Luisa Yuliana (2019)
The learning session entitled "We dramatized a tale: Party in the sky", was developed in the area of communication, taking into account the competence is expressed orally in their mother tongue, getting children to use gestures and make body movements that emphasize what it says, maintaining eye contact with their interlocutors. Also, they use their voice to convey emotions, characterize characters and give clarify to what it says._x000D_ The proposal has taken into account the pedagogical and didactic processes of the area, as well as the guidelines provided by the Ministry of Education for the development of competences, from a formative approach; the same that are constituted in both the theoretical and pedagogical foundation of the work._x000D_ The session has been planned considering the communicative approach of the area, its pedagogical processes such as motivation, exploration of knowledge, problematization, management and accompaniment, evaluation and transfer; in the didactic processes of the area has been planned strategies so that the child expressed orally before, during and after the experience lived.